Prose and Poetry for Teachers: An Overview of the Irish-Language Requirement (SCG) Literature Syllabus. - Whelton, Marie; Mac Suibhne, Aodán; Mac Giolla Bhríghde, Peadar (Irish National Teachers' Organisation, 2020)
To attain An Cháilíocht sa Ghaeilge (SCG), teachers who qualify abroad are required to read, study and analyse six prescribed Irish-language prose pieces and ten Irish-language poems. This article gives a brief overview of the syllabus by classifying the texts according to theme.
Keywords: Poetry; Prose; An Cháilíocht sa Ghaeilge (SCG); SCG literature syllabus; Irish-language poetry; Irish-language prose; Teacher education; Education--Ireland